Exploring global research status and trends in anti-obesity effects of traditional Chinese medicine through intestinal microbiota: a bibliometric study - Huang, Wenjing; Wang, Jiuyuan; Kuang, Min; Xiao, Zixuan; Fan, Boyan; Sun, Guixiang; Tan, Zhoujin (Frontiers in Cellular and Infection Microbiology, 2023)
Background The intestinal microbiota (IM) has been found to contribute to metabolic disorders that lead to excessive fat accumulation, systemic and chronic low-grade inflammation, and insulin resistance in the host. Current research highlights a pivotal interaction between IM and traditional Chinese medicine (TCM) in mitigating obesity-related diseases. Undeniably, IM stands as a central focus in TCM research aimed at preventing and treating obesity. Therefore, tracing the progress and trends in this field can offer valuable references and insights for future studies. Methods On June 17, 2023, we conducted a literature search on the topic of “IM and obesity in TCM” spanning the period from 2009 to 2023. We extracted the primary information of the publications, which includes complete records and reference citations, from the Science Citation Index Expanded (SCI-E) within the Web of Science Core Collection (WoSCC). To visualize and analyze the literature, we utilized CiteSpace and VOSviewer for bibliometric analysis. Results During the past fifteen years, a rapid increase in the number of publications has been observed. The cooperative networks demonstrate China, Beijing University of Chinese Medicine, and Food & Function as the most active countries, organizations, and journals in this field, respectively. Liu Bin has contributed the most publications. A paper by Xu Jia, published in 2014, holds the highest Local Citation Score (LCS). Analyses of keyword co-occurrence and reference co-citation indicate that the research hotspots of IM and obesity in TCM are primarily focused on the metabolic benefits driven by endogenous functional metabolic molecules generated by TCM regulation of IM. Other focal points include the mechanism by which TCM regulates IM to restore the intestinal mucosal barrier This is a provisional file, not the final typeset article, and manages the gut-organ axis, the metabolic advantages of acupuncture’s regulation of IM, and the process by which Chinese medicine small molecules transform IM. Conclusion This research offers a comprehensive understanding of the current status, hotspots, and trends in global TCM research. Additionally, it provides a comprehensive summary and exploration of the latest advancements in this field, thereby emphasizing the essence of TCM more effectively.